Towards Requirements Engineering Practice for Professional End User Developers: A Case Study - Faily, S (IEEE, 2008)
End-User Development has received a lot of attention in the research community. Despite the importance of Requirements Engineering in the software development life-cycle, comparatively little exists in the way of prescriptive advice or case studies on both Requirements Engineering and End-User Development. This paper argues that end-user developers can obtain practical benefit by adopting professional Requirements Engineering practices. We report on how these practices were fostered within a workplace environment and illustrate that evaluating the effectiveness of teaching such practices can lead to a better understanding of the relationship between End-User Development and Software Engineering in general.